Lumbar degenerative disease treated by percutaneous endoscopic transforaminal lumbar interbody fusion or minimally invasive surgery-transforaminal lumbar interbody fusion: a case-matched comparative study - You-Di Xue (BMC, 2021)
Abstract Purpose This study aimed to evaluate the clinical efficacy and imaging results of percutaneous endoscopic transforaminal lumbar interbody fusion (PETLIF) through comparing it with minimally invasive surgery-transforaminal lumbar interbody fusion (MISTLIF). Materials and methods We performed a retrospective analysis on patients with lumbar degenerative disease treated by PETLIF or MISTLIF from September 2017 to January 2019, and the patients were divided into two groups: the PETLIF group and the MISTLIF group. The clinical and imaging parameters of the two groups were evaluated. Results There was no significant difference between the two groups in operative time and complication rate. The estimated blood loss and the length of hospital stay in the PETLIF group were significantly better than those in the MISTLIF group. Compared with those before operation, the postoperative VAS-L and VAS-B scores were significantly improved after operation in the both groups. In addition, the postoperative VAS-B score of the PETLIF group was significantly lower than that of the MISTLIF group. At the last follow-up, there was no significant difference between the two groups in the VAS-L score, VAS-B score, ODI score, and bony fusion rate. Conclusions Both PETLIF and MISTLIF could achieve satisfactory clinical outcomes in the treatment of lumbar degenerative disease, but our study suggested that PETLIF had less damage, rapid recovery after operation, and short discharge time.